STUDI KINETIKA PENYISIHAN ORGANIK PADA SEQUENCING BATCH REACTOR (SBR) AEROB DENGAN PARAMETER RASIO WAKTU PENGISIAN TERHADAP WAKTU REAKSI - Mindriany Syafila (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
This kinetic study was done using two kind of variations, namely loading variations (600, 1800, 3400 and 4800 mg/l COD) and fill-react ratio variations (2:2, 2:4, and 2:8) by investigating main parameters, namely COD, VSS and total volatile acid (TVA), beside the other data such as CO2, gas concentration, DO, temperature and pH. And to investigate the role of microorganism, control was conducted with the absence of biomass. During filling period, the yield coefficient was 0,42-0,88 gVSS/gCOD. During reacting period, the yield coefficient was 0,39-0,93 gVSS/gCOD and specific biomass decay rate constant (Kd) 0,021 hour-1.